EXPERIENCE OF DISASTER NURSING SIMULATION BASED ON THEORY PLANNED BEHAVIOUR (TPB) IN THE CITY OF MEDAN - Hutajulu, Johansen; Hassan, Hafizah Che; Ompusunggu, Tanti Yosepha (Jurnal Online Keperawatan Indonesia, 2023)
Disaster is an event or series of events that threaten and disrupt people's lives and livelihoods caused by both natural and/or non-natural factors. Medan North Sumatera is one of the regions in Indonesia with a potential disaster that has the worst impact. Preparing the community to face a disaster has a very important role in mitigating the impact of a disaster. A nurse needs to have knowledge and skills regarding disaster and disaster management. The purpose of this study was to explore experience of disaster nursing simulation  based on theory planned behaviour (TPB) in the city of medan. Methods The research uses qualitative methods. The population in this study were nurses in the city of Medan with the 9 participants, selected only 9 had been interview with saturate data. The themes explored through are on Theory Planned Behavior. The themes of the research results obtained are: General Attitude, Religiosity, Socio Cultural, Experience, Attitude Toward Behaviour, Subjective Norm, Perceived Behaviour Control, Intention, Behaviour. With this Disaster Nursing Simulation, many nurses already have the provision of knowledge about disaster management, disaster response attitudes, and then  when a disaster occurs, them are involved when a disaster occurs. The themes obtained influence a person to behave and have an intention in disaster response, but in the end it is not necessarily someone who wants to take disaster response actions according to their intentions.